Review: Current trends, challenges, and success stories in adjuvant research - Singleton, Kentner L.; Joffe, Ari; Leitner, Wolfgang W. (Frontiers in Immunology, 2023)
Vaccine adjuvant research is being fueled and driven by progress in the field of innate immunity that has significantly advanced in the recent two decades, with the discovery of countless innate immune receptors and innate immune pathways. Receptors for pathogen-associated molecules (PAMPs) or host-derived, danger-associated molecules (DAMPs), as well as molecules in the signaling pathways used by such receptors are a rich source of potential targets for agonists that that enable the tuning of innate immune responses in an unprecedented manner. The targeted modulation of immune responses is achieved not only through the choice of immunostimulator – or select combination of adjuvants – but also through formulation and systematic modifications of the chemical structure of immunostimulatory molecules. The use of medium and high-throughput screening methods for finding immunostimulators has further accelerated the identification of promising novel adjuvants. Despite the progress that has been made in finding new adjuvants through systematic screening campaigns, the process is far from perfect, and a major bottleneck that significantly slows the process of turning innate immune receptor agonists into vaccine adjuvants continues to be the lack of in vitro correlates of in vivo adjuvanticity. This brief review discusses recent developments, trends, and successes in the adjuvant research field, without ignoring challenges and areas for improvement.